Making Space for the Dead : Catacombs, Cemeteries, and the Reimagining of Paris, 1780-1830 - Legacey, Erin-Marie, 1979- (Book collections on Project MUSE., 2019)
"This book unearths the revolutionary history of Paris's most famous spaces for the dead, including Pere Lachaise Cemetery and the Paris Catacombs, and explains how they became powerful sources of collective identity for modern France"--